KONTRIBUSI HERMENEUTIK HANS-GEORG GADAMER BAGI DIALOG ANTARAGAMA DI INDONESIA - Halomoan Londok (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Abstract This article aims to explain the role of Hans-Georg Gadamer’s hermeneutic in Interreligious Dialogue. There is a fundamental thing in dialogue that anyone will faced principle different from relation to other religion. Therefore, In interreligious Dialogue everyone or a religious person must be courageous to conversation their difference to the other religious person. The fundamental thing of Interreligious dialogue is how to understand diffrence and the recognition? To answer this question, I will elaborate hermeneutic of Gadamer on understanding the other in dialogue. I use a library study approach in qualitative methode. The result of Gadamer’s hermeneutic contributed to the perspective of certainly difffrence to understand diversity. Furthermore, his hermeneutic emphasized perspective of dialogue in temporal area not only belong to intelectual but also belong to non-intelektual.